Clinical Pattern Characterization of Cattle Naturally Infected by BTV‐8. Issue 3 (10th May 2012) - Zanella, G.; Martinelle, L.; Guyot, H.; Mauroy, A.; De Clercq, K.; Saegerman, C.
Summary Forty‐one cattle from seven Belgian farms and two French farms confirmed as infected with bluetongue virus serotype 8 (BTV‐8) were monitored from the onset of clinical signs to describe the disease pattern and estimate the duration of blood RT‐qPCR and competitiveELISA positivity under field conditions. On each visit, blood samples were taken, and a standardized clinical form was filled in for each animal. A clinical score was calculated for every week until the end of clinical signs. A classification and regression tree (CART) analysis was conducted to determine the most important clinical signs every week for the first 7weeks. The highest scores were recorded within 2 weeks of clinical onset. The first recorded clinical signs were quite obviously visible (lethargy, conjunctivitis, lesions of nasal mucosa, nasal discharge). Skin lesions, a drop in milk production and weight loss appeared later in the course of the disease. A biphasic pattern regarding nasal lesions was noticed: the first peak concerned mainly congestive and ulcerative lesions, whereas the second peak mainly concerned crusty lesions. The median time estimated by survival analysis to obtain negative RT‐qPCR results from the onset of clinical signs was 195 days (range 166–213 days) in the 23 cattle included in the analysis. Serological results remained strongly positive until the end of the study. These results should ensure more accurate detection of an emerging infectious disease and are of prime importance in improving the modelling of BTV‐8 persistence in Europe.